Two European Conflicts Conventions - Juenger, Friedrich K (Victoria University of Wellington Law Review, 1998)
The states of the European Union have so far concluded two major conflict of laws conventions: The Brussels Convention on Jurisdiction and the Enforcement of Judgments in Civil and Commercial Matters, and the Rome Convention on the Law Applicable to Contractual Obligations. Professor Juenger here reflects on the creation and experience of these treaties and concludes that the Brussels/Lugano Conventions present a model for the world while the Rome Convention shows what to avoid.